Picornavirus internal ribosome entry segments: comparison of translation efficiency and the requirements for optimal internal initiation of translation in vitro. - Borman, A M (1995)
On the basis of primary sequence comparisons and secondary structure predictions, picornavirus internal ribosome entry segments (IRESes) have been divided into three groups (entero- and rhinoviruses; cardio- and and aphthoviruses; and hepatitis A virus). Here, we describe a detailed comparison of the ability of IRESes from each group to direct internal initiation of translation in vitro using a single dicistronic mRNA (the only variable being the IRES inserted into the dicistronic region). We studied the influence of various parameters on the capacity of six different picornaviral IRESes, and the non-picornaviral hepatitis C virus IRES, to direct internal initiation of translation: salt concentration, the addition of HeLa cell proteins to rabbit reticulocyte lysate translation reactions, the presence of foot-and-mouth disease virus Lb or human rhinovirus 2A proteinase. On the basis of the characteristics of IRES-driven translation in vitro, the picornaviral IRESes can be classified in a similar manner to when sequence homologies are considered. IRESes from each of the three groups responded differently to all of the parameters tested, indicating that while all of these elements can direct internal ribosome entry, the functional requirements for efficient IRES activity vary dramatically. In the individual optimal conditions for translation initiation, the best IRESes were those from the cardio- and aphthoviruses, followed by those from the enteroviruses, which exhibited up to 70% of the efficiency of the EMCV element in directing internal initiation of translation.